Pengembangan Bermain Bowling Dalam Meningkatkan Kemampuan Mengenal Angka Pada Anak Kelompok A Ba Aisyiyah Wunut Tulung Klaten - Noor, Fu'ad Arif; Suwanti, Sri (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2021)
The problem in the research is that group A students at BA Aisyiyah Wunut Tulung Klaten, do not yet have the ability to recognize optimal numbers in terms of mentioning numbers 1 to 10, counting objects, mentioning the order of objects, and connecting objects with number symbols. So how is the implementation of playing bowling to improve the ability to recognize numbers in group A children at BA Aisyiyah Wunut Tulung Klaten. And how to increase the ability to recognize numbers through bowling for group A children at BA Aisyiyah Wunut Tulung Klaten.The purpose of this study was to determine the implementation of bowling in improving the ability to recognize numbers in children of group A in BA Aisyiyah Wunut Tulung Klaten and to determine the increase in ability to recognize numbers through bowling in children of group A in BA Aisyiyah Wunut Tulung Klaten. This study used a classroom action research (CAR) approach with 16 children in group A at BA Aisyiyah Wunut Tulung Klaten as research subjects. The research was carried out in two cycles, using qualitative data collection techniques with observation, interviews and documentation.The results showed that the implementation of learning to recognize numbers by playing bowling made the children of group A in BA Aisyiyah Wunut Tulung Klaten interested, which can be seen from the results of research with completeness before the action reached 0%, increased in cycle 1 it reached 25%, in cycle 2 it reached 50 %, so the child's ability to recognize numbers from pre-action and cycle II has increased by 50%.